Recovering lithium cobalt oxide, aluminium, and copper from spent lithium-ion battery via attrition scrubbing - Widijatmoko, Samuel D.; Fu, Gu; Wang, Zheng; Hall, Philip (2020)
In this manuscript, the results show that the single-stage liberation by using a cutting mill is sub-optimum. From the analysis, that the size fraction of < 850 µm only recovers 43.7 wt% LiCoO2. With the recovery of 9.0 wt% aluminium and 10.6 wt% copper the remainder of the copper being in the > 850 µm size fraction. The low recovery of LiCoO2 is caused by the particles that are still adhering on to the surface of the aluminium current collector. This lack of liberation prompted the use of attrition scrubbing as a secondary stage of mechanical treatment. 2.5 min Attrition scrubbing improves the selective liberation of cobalt towards aluminium and copper by 36.6 % and 42.6 % respectively. Attrition induces abrasion and it is shown to liberate the LiCoO2 particles. Results show a minimum of 80 wt% LiCoO2 particles can be recovered in the size fraction of < 38 µm with 7.0 wt% aluminium and 6.1 wt% copper recovery, making attrition scrubbing a suitable second stage mechanical treatment for the recovery of LiCoO2.